Pengaruh Instagram terhadap Peningkatan Pendapatan Bisnis Syariah (Studi Kasus Mahasiswa Sekolah Tinggi Ekonomi Syariah Islamic Village Tangerang - Banten) - Sunardi Sunardi; Samsudin Samsudin (ISLAMINOMICS: JOURNAL OF ISLAMIC ECONOMICS, BUSINESS AND FINANCE, 2020)
Instagram is one of the social media platforms that quite popular among millennials, Instagram also could be used as an effective and efficient promotional media. Instagram also could be used by anyone without the need for special skills in supervision. This research aims to see whether the use of Instagram has an influence towards the Increase of Sharia Business Income in Islamic Village School of Islamic Economics students in Tangerang. The study was conducted by distributing questionnaires to all students of the Islamic Economic Higher Education, Tangerang, and 80 respondents, consisting of semester 4, semester 6 and semester 8 respondents as part of this study. This research used quantitative method with statistical testing using a simple linear regression model with the dependent variable is Sharia Business Income (Y) and the independent variable is Instagram testing (X), which is carried out using IBM SPSS 22 software. The results show that the Instagram variable (X) has an influence on the Sharia Business Income variable (Y). This is evidenced by the regression results which show the Instagram variable (X) statistically has a t count value of 5.680 and a t table value of 1.664, this indicates that t count> fromt table so that ???????? is accepted and ????o is rejected and it can be denied that Instagram has significant influence on the increase in Sharia Business Income at the College of Sharia Economics, Islamic Village, Tangerang and the results of the analysis of the coefficient of determination (R2), Instagram has a direct influence on Sharia Business Income by 29.3%, while the remaining 70.7% (100% - 29.3%) by other variables not examined in this study.